An update of anthropogenic CO2 storage rates in the western South Atlantic basin and the role of Antarctic Bottom Water - Ríos, Aida F.; Velo, A.; Pardo, Paula C.; Hoppema, Mario; Pérez, Fiz F. (Journal of Marine Systems, 2012)
7 páginas, 4 tablas, 3 figuras, 1 apéndice.-- Proyecto Carbochange The western basin of the South Atlantic from 10°N to 55°S and from the coast to the Mid-Atlantic Ridge is a region with large uncertainties as to the storage of anthropogenic CO2 (Cant). Our analysis of data of the last three decades provides a Cant storage rate of 0.92±0.13 mol m−2 y−1, i.e., 13%–35% higher than previous estimates in this area. The low but significant Cant concentrations ([Cant]) in the large volume of relatively well ventilated Antarctic Bottom Water (AABW) may well be the underlying cause of this higher storage rate. In fact, the significant contribution in terms of Cant of this ventilated AABW that enters the western South Atlantic Ocean was calculated to be 0.055±0.02 Pg C y−1 or 0.20 mol m−2 y−1. Instead of being based on the annual trend, the Cant specific inventory (in mol m−2) evolution is more consistently computed as a function of the atmospheric xCO2 perturbation in ppm, (0.64 mol m−2 ppm−1). This methodology allows improved projections of Cant storage rates over long periods. EU FP7 project CARBOCHANGE “Changes in carbon uptake and emissions by oceans in a changing climate” which received funding from the European Community's Seventh Framework Programme under grant agreement no. 264879 Peer reviewed